Second Five Year Plan (Draft) Plan Volume II Government of Himachal Pradesh - Planning Commission (Planning Commission, 1955)
Agriculture is the main stay of more than about 94 per pent of population of Himachal Pradesh, The national income in Himachal Pradesh is mainly derived directly or indirectly through the agricultural sources. There are no immediate prospectus to establish large industries which can divert a part of the population of the State towards industrial sector. The small industrial developmental schemes and cottage industries are likely to provide additional sources of income to already impoverished agriculturists in the State rather than large scale employment. The average holdings of about 0.6 acres per capita, often carved out of the hill sides provide, bare sustenance.
Government of Himachal Pradesh
Government of Himachal Pradesh
Keywords: Land Improvement Scheme; Supply Scheme; Fertilizer Scheme; Seed Distribution Scheme; Scheme for Survey; Manufacture and Distribution of Improved Implements; Fruit Research & Development Scheme; Scheme for Training of Mails; Scheme for Establishment of Squad of skilled Personnel; Fruit and Vegetable Preservation Scheme; Scheme for Agro-Economic Enquiry; Compost Scheme; Agricultural Marketing Scheme